The House of David : between political formation and literary revision - Leonard-Fleckman, Mahri (Fortress Press, 2016)
Mahri Leonard-Fleckman compares the "house of . . ." terminology in the ninth-century Tel Dan inscription with early first-millennium Assyrian usage and examines the "house of David" in 2 Samuel and 1 Kings. She argues that the "house of David" was a small body politic around David, but distinct from any Judean dynastic context. The equation with Judah with a later southern kingdom resulted from the redactional creation of a Davidic coterie